2020
DOI: 10.1177/0020764020916745
|View full text |Cite
|
Sign up to set email alerts
|

How can today’s substance-using youth be helped to quit? Perspectives of college students from Bangalore, India

Abstract: Background: Substance use among college students is increasing, yet research regarding their viewpoints on how they can be helped is sparse in India. Aim: The purpose of this study was to explore in depth the perspectives of college students as to how college youth can be helped to quit the use of psychoactive substances. Method: Data from focus group interviews with 38 adolescent college students were analyzed qualitatively to identify their viewpoints on how today’s college youth can be helped to quit substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…[97] A qualitative study echoed our findings that mental health and mental illness were unclear concepts and were associated with acute problems, such as 'brain deficiency or dysfunction and abnormal behaviour.' [98] Another qualitative study found that college students believed that using substances helped to relieve depression, enhance health and lose weight and that using in small quantities did not cause harm [99]. The study suggests that future interventions should be non-judgemental, student-friendly, relatable and 'specific to the youth's life circumstances and needs.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…[97] A qualitative study echoed our findings that mental health and mental illness were unclear concepts and were associated with acute problems, such as 'brain deficiency or dysfunction and abnormal behaviour.' [98] Another qualitative study found that college students believed that using substances helped to relieve depression, enhance health and lose weight and that using in small quantities did not cause harm [99]. The study suggests that future interventions should be non-judgemental, student-friendly, relatable and 'specific to the youth's life circumstances and needs.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A qualitative study of 38 adolescents using focus interviews found that academic pressure is a major source of stress. These adolescents attempted to relieve stress by using substances, especially when they felt that they could not succeed ( 73 ). Furthermore, with decreased parental supervision and increased autonomy, a small number of students who enter university may exhibit more participation in high-risk behaviors such as drug use ( 74 , 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…(b) Focus group discussions (FGDs) with college students: The development of the skill-based intervention was heavily informed by the results of FGDs which we conducted earlier with college students. [ 9 ]…”
Section: Methodsmentioning
confidence: 99%
“…The college students who participated in the FGDs[ 9 ] were invited to participate in the pilot-testing of the intervention, since their inputs had been instrumental in its development. Twenty-three of the original 38 college students agreed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation